Ranolazine protects from doxorubicin‐induced oxidative stress and cardiac dysfunction. (6th January 2014) - Tocchetti, Carlo G.; Carpi, Andrea; Coppola, Carmela; Quintavalle, Cristina; Rea, Domenica; Campesan, Marika; Arcari, Antonella; Piscopo, Giovanna; Cipresso, Clemente; Monti, Maria Gaia; De Lorenzo, Claudia; Arra, Claudio; et al.
Abstract : Aims: Doxorubicin is widely used against cancer; however, it can produce heart failure (HF). Among other hallmarks, oxidative stress is a major contributor to HF pathophysiology. The late I Na inhibitor ranolazine has proven effective in treating experimental HF. Since elevated [Na + ]i is present in failing myocytes, and has been recently linked with reactive oxygen species (ROS) production, our aim was to assess whether ranolazine prevents doxorubicin‐induced cardiotoxicity, and whether blunted oxidative stress is a mechanism accounting for such protection. Methods and result: In C57BL6 mice, doxorubicin treatment for 7 days produced LV dilation and decreased echo‐measured fractional shortening (FS). Ranolazine (305 mg/kg/day) prevented LV dilation and dysfunction when co‐administered with doxorubicin. Doxorubicin‐induced cardiotoxicity was accompanied instead by elevations in atrial natriuretic peptide (ANP), BNP, connective tissue growth factor (CTGF), and matrix metalloproteinase 2 (MMP2) mRNAs, which were not elevated on co‐treatment with ranolazine. Alterations in extracellular matrix remodelling were confirmed by an increase in interstitial collagen, which did not rise in ranolazine‐co‐treated hearts. Levels of poly(ADP‐ribose) polymerase (PARP) and pro‐caspase‐3 measured by western blotting were lowered with doxorubicin, with increased cleavage of caspase‐3, indicating activation of the proapoptotic machinery. Again, ranolazine prevented this activation. Furthermore, in HL‐1 cardiomyocytes transfected with HyPer to monitor H2 O2 emission, besides reducing the extent of cell death, ranolazine prevented the occurrence of oxidative stress caused by doxorubicin. Interestingly, similar protective results were obtained with the Na + /Ca 2+ exchanger (NCX) inhibitor KB‐R7943. Conclusions: Ranolazine protects against experimental doxorubicin cardiotoxicity. Such protection is accompanied by a reduction in oxidative stress, suggesting that I Na modulates cardiac redox balance, resulting in functional and morphological derangements.